Upaya Mewujudkan Peran Edukasi Melalui Budaya Berfikir Di Museum Biologi Yogyakarta - Ani Wijayanti - AKPAR BSI Yogyakarta; Janianton Damanik; Chafid Fandeli; Sudarmadji - UGM (Khasanah Ilmu - Jurnal Pariwisata Dan Budaya, 2017)
Abstract - Biology museum is a special museum of biological education that presents a collection of objects of various flora and fauna preserved. The museum is a study destination for school students and researcher. This research is a qualitative descriptive, which is the researcher as an instrument. Respondents were chosen by purposive method of snowball sampling, i.e the students as informants. Data were analyzed by reduction system. The result of data analysis is known that the collection objects of Biology museum more than 4000 can be understood well by the students through the culture of thinking during the visit at the Biology museum. The culture of thinking can be developed through eight aspects, namely; expectations, opportunities, time, modeling, routines, language, environment, and relationships.Keywords : Educational, Culture of thinking, museum.Abstrak - Museum Biologi UGM merupakan museum khusus pendidikan hayati yang menyajikan benda koleksi berupa awetan flora dan fauna yang beranekaragam. Museum ini menjadi tujuan wisata studi bagi para siswa sekolah dan penelitian bagi para mahasiswa. Penelitian ini merupakan deskriptif kualitatif, dengan peneliti sendiri sebagai instrumen. Responden dipilih dengan cara purposive yang bersifat snowball sampling, yakni para siswa sebagai informan. Data dianalisis dengan sistem reduksi. Hasil analisis data diketahui bahwa benda koleksi museum Biologi yang berjumlah lebih dari 4000 dapat dipahami dengan baik oleh para siswa melalui budaya berfikir selama kunjungan di museum Biologi. Budaya berfikir sendiri dapat dikembangkan melalui delapan aspek, yakni; harapan, peluang atau kesempatan, waktu, pemodelan, rutinitas, bahasa, lingkungan, hubungan atau relasi.Kata Kunci : Edukasi, Budaya berfikir, Museum